Profile of surgical site infections in gynecology and obstetrics in a public teaching hospital (Research, Society and Development, 2021)
The aim of the study was to identify surgical site infections related to gynecological and obstetric procedures. Method: documentary, cross-sectional, retrospective and quantitative study. The SSI were analyzed between March 2017 and March 2019. The study variables were: age, anatomical planes involved, surgical procedure, confirmation criteria, isolated microorganism, case outcome and time of outpatient return. Descriptive analysis was used for data exploration. Results: 322 cases of SSI were reported, 41% of which were gynecological-obstetric. The ISC rate was calculated at 1.5%. The most affected age group was 21 to 30 years, with a predominance of superficial incisional infections (63%), clinically diagnosed (97%), especially cesarean delivery (90%). Most patients (68%) returned for postoperative evaluation within ten days, with clinical discharge (100%). Conclusion: despite the disclosure of diagnostic criteria, the SSI were high in the hospital under study, indicating the need to adopt preventive protocol measures.